The Placenta Regulates Intrauterine Fetal Growth via Exosomal PPARγ - Xiaofang Luo; Biao Huang; Ping Xu; Hao Wang; Baozhen Zhang; Li Lin; Jiujiang Liao; Mingyu Hu; Xiyao Liu; Jiayu Huang; Yong Fu; Mark D. Kilby; et al. (Advanced Science)
Abstract Abnormal adipogenesis is a major contributor to fetal growth restriction (FGR) and its associated complications. However, the underlying etiology remains unclear. Here, it is reported that the placentas of women with pregnancies complicated with FGR exhibit peroxisome proliferator‐activated receptor γ (PPARγ) inactivation. In mice, trophoblast‐specific ablation of murine PPARγ reproduces the phenotype of human fetuses with FGR and defective adipogenesis. Coculture of trophoblasts with preadipocytes significantly improves preadipocyte commitment and differentiation and increases the transcription of a series of adipogenic genes via intercellular transfer of exosomal PPARγ proteins. Moreover, nanoparticle‐mediated placenta‐specific delivery of rosiglitazone (RGZ) significantly rescues adipogenesis defects in an FGR‐induced mouse model. In summary, the placenta is a major reservoir of PPARγ. An insufficient supply of placental PPARγ to fetal preadipocytes via exosomes during late gestation is a major mechanism underlying FGR. Preclinically, placenta‐targeted RGZ administration can be a promising interventional therapy for FGR and/or defective intrauterine fat development.